In quest of lost worlds : five archeological expeditions, 1925-1934 - Khun de Prorok, Byron, 1896-1954 (Narrative Press, 2001)
The stories from four of de Prorok's expeditions: the discovery of Tin Hinan's tomb in the Sahara, his excavation of the temple of Jupiter Ammon in Libya, his search for the stone-age Lacandon Indians in Chiapas, Mexico, and his quest for King Solomon's mines in Ethiopia.